A Generative Theory of Tonal Music - Lerdahl, Fred 1943-; Jackendoff, Ray 1945- (Cambridge, MA MIT Press, 1983)
A classic in music theory since its publication in 1981, this work models music understanding from the perspective of cognitive science. The point of departure is a search for a grammar of music with the aid of generative linguistics. The theory, which is illustrated with numerous examples from Western classical music, relates the aural surface of a piece to the musical structure unconsiously inferred by the experienced listener. From the viewpoint of traditional music theory, it offers many innovations in notatation as well as in the substance of rhythmic and reductional theory.
Keywords: Music theory; Linguistics; Music psychology